Association Between Sociodemographic Status and Physical Functioning of Obese School Going Children- A Cross Sectional Study (Journal of Rangpur Medical College, 2024)
Background: Obesity is major non-communicable disease (NCD) all over the world affecting both children & adult. More than 30 million overweight children are living in developing countries & 10 million in developed countries. Childhood obesity leads to a significant reduction in health-related functioning. So, the negative effects of childhood obesity on quality of life (QoL) have to be determined to combat the problem. Objective: To determine the association between sociodemographic status and physical functioning of obese school going children. Methods: This was a cross sectional type of descriptive study conducted at different schools of Rajshahi city from June 2015 to September 2015. Four (4) schools were selected- a) Govt. Laboratory High School, Rajshahi b) Rajshahi Collegiate School c) River view Collectorate School, Rajshahi and d) Rajshahi University School. The study population were 5 to 15 years old obese school children. A total number of 221 children were interviewed. Results: The ages of the respondents were between 4 to 15 years, and the mean age was 7.83±3.058 years. Among the 221 respondents more than half (56.6%) were in 4-7 years of age group, another 24.0% belonged to the age group of 8- 11 years and only 19.5% were 12- 15 years age group. Weight of the respondents was from 20 to 65 kg and mean weight of the respondents was (41.64±10.75). Here, 36.2% weight was from 37-47 kg and 29.0% weight was from 26-36 kg. Another 23.1%, 7.7% and 4.1% weight was from 48-58 kg, 59-69 kg and 15-25 kg respectively. There was no significant relationship with respondent age and sex with physical functioning (p ≥ 0.05). There was a significant relationship with weight and physical functioning (p≤0.05). Conclusions: The sociodemographic status may influence the physical functioning of the obese school going children. Their lifestyle must be modified in this early life otherwise they will be affected by different non communicable diseaseJ Rang Med Col. March 2024; Vol. 9, No. 1: 71-76